PEDAGOGICAL ESSENCE OF DEVELOPING TECHNOLOGICAL COMPETENCE IN STUDENTS - Butaeva Nargiza Buriboyovna (Western European Studies, 2024)
Students of technical higher education institutions have the flexibility of thinking and the mobility of decision-making, the ability to revise the accumulated experience and advanced ideas, to design the production process based on modern technologies, it requires the training of qualified specialists, whose abilities and capabilities are taken into account. From this point of view, it is necessary to train students appropriately based on a systematic approach in the process of education and training to become modern specialists
Keywords: Technological competence; students; professional knowledge